Dietary patterns in mild cognitive impairment and dementia in older adults from Yucatan, Mexico - Garrido-Dzib, Angel Gabriel; Palacios-González, Berenice; Ávila-Escalante, María Luisa; Bravo-Armenta, Erandi; Avila-Nava, Azalia; Gutiérrez-Solis, Ana Ligia (Frontiers in Nutrition, 2024)
Background: Some dietary patterns and dietary components have an important role in preventing and helping to improve patients' quality of life of individuals with Mild Cognitive Impairment (MCI) and dementia. In Mexico, it is unknown what the dietary patterns are among older adults with MCI and dementia. We aimed to identify the dietary patterns of older adults with MCI and dementia living in Yucatan, Mexico. Methods: A cross-sectional study was carried out among 39 patients as controls and 34 individuals as cases (MCI and dementia). A food frequency questionnaire collected diet information, anthropometric and clinical parameters, and lifestyle characteristics. The dietary patterns were evaluated through Partial Least-Squares Discriminant Analysis (PLS-DA). Results: The food groups that showed discrimination between groups and were classified into the dietary patterns of MCI and dementia individuals were "pastries and cookies," "soups," and "legumes." The dietary pattern of older adults without cognitive impairment was characterized by "nuts and seeds," "candies," "vegetables," "coffee and tea," and "water." The consumption of "pastries and cookies" showed an increasing correlation with serum insulin levels (r = 0.36, P = 0.01), and "soups" showed an inverse correlation with total cholesterol levels (r = -0.36, P = 0.02) in patients with MCI and dementia. In controls, there is a positive correlation between the consumption of "nuts and seeds" (r = 0.333, P = 0.01) and "vegetables" (r = 0.32, P = 0.02) with levels of urea; "coffee and tea" showed a positive association with levels of insulin (r = 0.378, P = 0.05). Conclusions: The dietary pattern of individuals with MCI and dementia has some nutritional deficiencies. Including an adequate intake of vegetables, fruits, and protein could improve the quality of life of subjects living with these conditions in Yucatan, Mexico.